Cryptic confusion. Issue 9 (12th August 2022) - Vonberg, Frederick; Dawson, Angelo; Scott, Gregory
Abstract : Neurotoxicity is often a late consideration, particularly if the neurotoxic agent is given with therapeutic intent, because the poisoning occurs without the diagnostic clues typical of an intentional attack. We present the case of a 76 year old woman with renal failure, who was admitted with confusion and hal- lucinations. Several days previously, she had started Aciclovir because of a vesicular rash. Her condition was attributed to varicella zoster encephalitis and she was switched from oral to intravenous Aciclovir. Two days later, and after peritoneal dialysis, she had deteriorated further, becoming completely unre- sponsive with upper limb myoclonus. The 9-Carboxymethoxymethylguanine (CMMG) level was elevated at 21.2 mg/L (normal <2mg/L). A diagnosis of Aciclovir-induced neurotoxicity (AIN) was made. Aciclovir was stopped, the patient received haemodialysis, and she made a significant recovery. AIN occurs almost exclusively in patients with renal failure. Reduced excretion of Aciclovir, or its prodrug Valaciclovir, results in the toxic accumulation of CMMG. Critically, peritoneal dialysis has little effect on removing Aciclovir. AIN is characterised by triad of hallucinations, involuntary movements, and delusions of death, including Cotard's syndrome. Diagnosis is challenging as AIN can resemble viral encephalitis. AIN should be considered in encephalopathic patients with renal failure who are taking Aciclovir.